Spaces 14, contemporary settings - De Haro, Fernando; Fuentes, Omar. ([Place of publication not identifed] : AM Editores, 2011)
Nobody has so far come up with a way of quantifying the benefits of good architectural design in financial analyses, but nobody will disagree that good design plays a crucial role in determining a project's success or failure. In a commercial area, it is the design's quality that will make people go there more often and spend more time there, as well as turn it into their favorite place for a great many years to come. The mood of people working in an office block and, hence, their productivity will be strongly influenced by the design. It also encourages good working relationships, makes us feel proud of our company and makes us happier in the place where we spend most of our lives. A well-designed hotel that connects travelers with the culture of the place they are visiting but, at the same time, also makes them feel at home, is without doubt a fundamental part of the traveling experience.